An experimental study the teaching of arithmetic in English versus the teaching of arithmetic in the vernacular for grades III and IV - Russell, Marian (George) 1918- (s.n.], 1967)
The study examined the levels of achievement in arithmetic of pupils of Grade III and IV in public schools in any Tagalog area with the purpose of ascertaining if there is any significant difference in achievement in using Tagalog, the natural dialect, or English, a foreign language, as the medium of intruction.